Diseño de una solución basada en el internet de las cosas (IoT) empleando Lorawan para el monitoreo de cultivos agrícolas en Perú - Aguilar Zavaleta, Samuel (2020)
The thesis has the fundamental purpose of defining the design of a solution based on the Internet of Things (IoT) using LoRaWAN technology to increase the monitoring and control indicators of the production parameters of agricultural crops in Peru. The research scenario is Pachacutec district, located in the province of Ica, department of Ica. The network architecture is defined, establishing the technical characteristics of the agricultural sensors, irrigation control circuit, communications equipment and cloud services required, for which 3 alternatives are analyzed in each case. Similarly, the operating frequency band for LoRaWAN technology in Peru and the energy requirements for field monitoring stations are determined. Link budget is calculated for LoRaWAN devices in the study area, obtaining path loss using the Okumura-Hata model, the maximum link distance and the field coverage. A coverage simulator is also used and similar results are achieved with it, validating the calculations obtained. A simulation of the proposed solution is developed. A LoRaWAN end node is simulated and a LoRaWAN and IoT servers hosted in computational clouds are used. Similarly, a mobile application is developed for Android, which allows access to the system, database, and information graphics. An economic-financial evaluation of the solution is carried out as a private project, based on the costs of investment, operation and projected income, determining the financial indicators for its evaluation. Finally, a Gantt chart is presented with the implementation schedule of the solution.